MAPLE I Study – Public Opinion Panel Survey on European Attitudes and Political Behaviour, 2019 - Lobo, Marina Costa (2023)
MAPLE investigates the salience and polarisation of the European issue, in the media, during electoral campaigns, and in parliamentary debates, in Belgium, Germany, Greece, Ireland, Portugal and Spain. This set of surveys was carried out in the six countries simultaneously in a two-wave panel in each country. The first wave occurred in January 2019 and the second wave occurred in June 2019. The surveys are drawn from qualtrics online panelsl and they follow a three crossed-quota design based on age (three categories), education (three categories) and gender (two categories). The study includes questions on attitudes towards the European Union and national politics, as well as political behaviour. Wave 1 of the panel also includes a conjoint experiment where respondents were asked to choose among different parties, based on a number of characteristics which were randomly assigned to parties. Wave 2 was carried out following the European Parliament Elections and includes a repetition of the questions in Wave 1 as well as several questions pertaining to vote recall for the EP elections. Para mais informação sobre o projeto: http://www.maple.ics.ulisboa.pt/.